Ekonomiczne podejście do wspólnotowych reguł konkurencji - Bazylińska-Nagler, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The author presents the process of transition from legalistic to economic approach in creating and application of the EU law on competition. The law on competition is a teleological law serving the purpose of economy, protecting proper functioning of market against abuse. Widely conceived law on competition plays a dual role, on the one hand combating dishonest competition on the part of participants in the market, on the other it is to prevent invalidating competition as a whole, ensuring proper functioning of free-market economy. The on-going process of modernisation of the EU competition policy aims at increasing the role of the economic analysis as a factor influencing legal framework.
Keywords: prawo konkurencji; Unia Europejska; ochrona konkurencji; ochrona konsumenta